The Epidemiologic and Pharmacodynamic Cutoff Values of Tilmicosin against Haemophilus parasuis - Zhang, Peng; Hao, Haihong; Li, Jun; Ahmad, Ijaz; Cheng, Guyue; Chen, Dongmei; Tao, Yanfei; Huang, Lingli; Wang, Yulian; Dai, Menghong; Liu, Zhenli; Yuan, Zonghui (Frontiers in Microbiology, 2016)
The aim of this study was to establish antimicrobial susceptibility breakpoints for tilmicosin against Haemophilus parasuis, which is an important pathogen of respiratory tract infections. The minimum inhibitory concentrations (MICs) of 103 H. parasuis isolates were determined by the agar dilution method. The wild-type (WT) distribution and epidemiologic cutoff value (ECV) were evaluated by statistical analysis. The new bronchoaveolar lavage (BAL) was used to establish intrapulmonary pharmacokinetic (PK) model in swine. The pharmacokinetic (PK) parameters of tilmicosin, both in pulmonary epithelial lining fluid (PELF) and in plasma, were determined using high performance liquid chromatography (HPLC) method and WinNonlin software. The pharmacodynamic cutoff (COPD) was calculated using Monte Carlo simulation. Our results showed that 100% of WT isolates were covered when the ECV was set at 16μg/mL. The tilmicosin had concentration-dependent activity against H. parasuis. The PK data indicated that tilmicosin concentrations in PELF was rapidly increased to high levels at 4 hours and kept stable until 48 hours after drug administration, while the tilmicosin concentration in plasma reached maximum levels at 4 hours and continued to decrease during 4-72 hours. Using Monte Carlo simulation, COPD was defined as 1 μg/mL. Conclusively, the ECV and COPD of tilmicosin against H. parasuis were established for the first time based on the MIC distribution and PK-PD analysis in the target tissue, respectively. These values are of great importance for detection of tilmicosin-resistant H. parasuis and for effective treatment of clinical intrapulmonary infection caused by H. parasuis.